Making money from waste: The economic viability of producing biogas and biomethane in the Idaho dairy industry. (15th July 2018) - Lauer, Markus; Hansen, Jason K.; Lamers, Patrick; Thrän, Daniela
Highlights: Anaerobic digestion can increase the income of (dairy) farmers. ≥3000 cows per farm are required for an economically viable plant operation. Joint, cooperative anaerobic digestion plants allows a higher manure utilization. Abstract: Farm operations in the USA and Europe have seen a radical change in the last decades: small sized farms are disappearing, and farm size and total livestock on larger farms are increasing. The resulting spatial density of animals causes several environmental impacts. Anaerobic digestion is one promising technical solution to alleviate most of these impacts while simultaneously providing a regional energy source. This analysis assesses the economic viability of using dairy-cow manure for either (i) the on-farm production and use of biogas to generate electricity and heat or (ii) the upgrading biogas to biomethane, a natural-gas substitute. A non-linear optimization model was developed to optimize plant capacity for anaerobic digestion and maximize the net present value for each option by farm size. In this study, we used Idaho's dairy farms as a case study. The analysis implies that at least 3000 cows per farm are required for an economically viable anaerobic-digestion plant operation. For farms with up to 3600 animals, the highest net present value was achieved for the on-farm use of biogas. Farms larger than that achieved their best economic results via the production of biomethane. In total about 45% of Idaho's dairy manure could be utilized by economically feasible biogas and biomethane plants. A higher manure utilization rate could be achieved through joint, cooperative anaerobic digestion plants and manure transportation. The results can be transferred to other regions and countries, respectively, to reduce the negative impact of intensive livestock farming.